Zona pellucida: An extracellular matrix with applications in the study of immunocontraception in domestic carnivores - Sánchez Riquelme, Alfonso; De los Reyes Solovera, Mónica (Revista Científica de la Facultad de Ciencias Veterinarias)
Zona pellucida (ZP) is an extracellular matrix surrounding the mammalian oocyte. In most mammalian species this matrix consists of three families of glycoproteins likely to suffer several postraductional modifications to acquire different immunological and biochemical properties. The ZP are involved in the initial recognition and binding events of sperm to oocyte investments. Because of its major role in the fertilization process (interaction with sperm, induction of acrosome reaction, control of polyspermy) the ZP has been used as an antigen to induce immunological response in order to produce female infertility, a relevant issue in domestic carnivores. Depending on the predominant immunological response (humoral or cellular) the infertility can be reversible (Immunocontraception) or irreversible (immunosterilization), respectively. Currently the goal is to develop recombinant ZP antigen with immunodominant epitopes in order to produce predictable and safely response.